Edge Pair Sum Labeling - Jeyanthi, P.; Devi, T. Saratha (Journal of Scientific Research, 2013)
An injective map f : E(G) ? {±1, ±2, ,±q } is said to be an edge pair sum labeling of a graph G(p, q) if the induced vertex function f*:V(G) ? Z {0} defined by f*(?) = ?e?E? f(e) is one-one, where denotes the set of edges in G that are incident with a vertex v and f*(V(G)) is either of the form {±k1, ±k2, , ±kp/2} or {±k1, ±k2, , ±k(p-1)/2}U{kp/2} according as p is even or odd. A graph with an edge pair sum labeling is called an edge pair sum graph. In this paper we prove that path Pn, cycle Cn, triangular snake, PmUK1,n, Cn?Kmc are edge pair sum graphs. Keywords: Pair sum graph, edge pair sum labeling, edge pair sum graph. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i3.15001 J. Sci. Res. 5 (3), 457-467 (2013)